2020
DOI: 10.14744/nci.2020.47154
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Endometrial Cancer In The Elderly Patient Group and Their Effects On Survival

Abstract: OBJECTIVE: The objective of the study was to investigate the prognostic factors of the elderly group and their effects on survival by examining the histopathological features, surgical treatment protocols, and treatment modalities of patients diagnosed with endometrial cancer (EC). METHODS: The records of 397 EC patients who completed their treatment and follow-up at a single center between 2012 and 2019 were evaluated retrospectively. The patients were evaluated in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…This study confirmed that elderly women had a higher incidence of deep myometrial invasion, serous tumour histology and p53abn tumours, as seen by others. 2,4,5,7 However, in this study the correlation between older age and more aggressive tumour characteristics does not entirely explain the poorer oncological outcomes in elderly women. Age was found to be an independent risk factor, after correcting for stage, histotype and grade, LVSI, molecular class, adjuvant treatment and competing events.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…This study confirmed that elderly women had a higher incidence of deep myometrial invasion, serous tumour histology and p53abn tumours, as seen by others. 2,4,5,7 However, in this study the correlation between older age and more aggressive tumour characteristics does not entirely explain the poorer oncological outcomes in elderly women. Age was found to be an independent risk factor, after correcting for stage, histotype and grade, LVSI, molecular class, adjuvant treatment and competing events.…”
Section: Discussioncontrasting
confidence: 57%
“…Nonetheless, many studies only evaluate the relation of age with overall survival. 2 Moreover, studies that do investigate recurrence or EC-specific survival often do not account for competing causes of death, which are more common in elderly, possibly leading to an overestimation of the impact of advanced age on prognosis.…”
Section: Introductionmentioning
confidence: 99%